Ergonomics and Usability – key factors in Knowledge Society - Nunes, Isabel Lopes (2008)
During the recent years human society evolved from the “industrial society age” and transitioned into the “knowledge society age”. This means that knowledge media support migrated from “pen and paper” to computer-based Information Systems. Due to this fact Ergonomics has assumed an increasing importance, as a science/technology that deals with the problem of adapting the work to the man, namely in terms of Usability. This paper presents some relevant Ergonomics, Usability and User-centred design concepts regarding Information Systems.